Association of Stress Hyperglycemia Ratio With Acute Ischemic Stroke Outcomes Post-thrombolysis - Shen, Chuan-Li; Xia, Nian-Ge; Wang, Hong; Zhang, Wan-Li (Frontiers in Neurology, 2022)
Background and Purpose: The association between stress hyperglycemia and clinical outcomes in patients with acute ischemic stroke treated with intravenous thrombolysis (IVT) is uncertain. We sought to analyze the association between the stress hyperglycemia ratio (SHR) using different definitions and clinical outcomes in acute patients with ischemic stroke undergoing IVT. Methods: A total of 341 patients with ischemic stroke receiving IVT were prospectively enrolled in this study. The SHR was evaluated using different equations: SHR1, fasting glucose (mmol/L)/glycated hemoglobin (HbA1c)(%); SHR2, fasting glucose (mmol/L)/[(1.59×HbA1c)-2.59]; SHR3, admission blood glucose (mmol/L)/[(1.59×HbA1c)-2.59]. Poor functional outcome was defined as a modified Rankin scale score of 3–6 at 3 months. Multivariate logistic regression analysis was used to identify the relationship between different SHRs and clinical outcomes after IVT. Results: A total of 127 (37.2%) patients presented with poor functional outcomes at 3 months. The predictive value of SHR1 for poor functional outcomes was better than that of SHR2 and SHR3 in receiver operating characteristic analyses. On multivariate analysis, SHR1 (odds ratio [OR] 14.639, 95% CI, 4.075–52.589; P = 0.000) and SHR2 (OR 19.700, 95% CI, 4.475–86.722; P = 0.000) were independently associated with an increased risk of poor functional outcome but not SHR3. Conclusions: Our study confirmed that the SHR, as measured by SHR1 and SHR2, is independently associated with worse clinical outcomes in patients with ischemic stroke after intravenous thrombolysis. Furthermore, SHR1 has a better predictive performance for outcomes than other SHR definitions.